Die Situation der Jugend in Dubrava (Zagreb) - Soziale Integration und Desintegration - Brčić, Carmen; Čaldarović, Ognjen (1999)
Major results on youth in Dubrava, Zagreb are presented, especially the results concerning the integration and separation of youth.
GER